Analog neuromorphic circuit for spontaneous Ca2+ oscillations - Beatriz O. Câmara; Janaina G. Guimarães; Marcelo L. Pereira Junior (Scientific Reports, 2023)
Abstract This study proposes an innovative analog neuromorphic circuit design to mimic spontaneous Ca2+ oscillations observed in astrocytes. Unlike traditional models, this approach does not rely on synaptic stimulation, suggesting that astrocytes may play a key role in generating neuronal activity. The circuit is built using transistor differential pairs to approximate the nonlinear sigmoidal biological functions, and its performance is validated through simulation and compared against mathematical models using phase diagram analysis. Results indicate a good fit between the circuit and the mathematical model. Finally, the circuit’s ability to simulate the release of glutamate and ATP through spontaneous oscillations is demonstrated.